Placement of an intrauterine device within 48 hours after second-trimester medical abortion : a randomized controlled trial - Hogmark, Sara; Rydelius, Johanna; Envall, Niklas; Teleman, Pia; Gemzell-Danielsson, Kristina; Kopp Kallner, Helena (American Journal of Obstetrics and Gynecology, 2024)
Background: International guidelines recommend placement of intrauterine devices immediately after second-trimester medical abortion, but evidence concerning the optimal time for intrauterine device placement is lacking from clinical trials. Objective: This study aimed to investigate effectiveness, safety, and acceptability of intrauterine device placement within 48 hours, compared with placement at 2 to 4 weeks after second-trimester medical abortion. We hypothesized that intrauterine device placement within 48 hours would be superior compared with placement at 2 to 4 weeks after the abortion, in terms of the proportion of intrauterine device use after 6 months, with maintained safety and acceptability. Study Design: In this open-label, randomized, controlled, superiority trial, we recruited participants at 8 abortion clinics in Sweden. Eligible participants were aged ≥18 years, requesting medical abortion with gestation ≥85 days, and opting for use of a postabortion intrauterine device. Participants were randomized (1:1) to intrauterine device placement either within 48 hours of complete abortion (intervention) or after 2 to 4 weeks (control). Our primary outcome was self-reported use of an intrauterine device after 6 months. Secondary outcomes included expulsion rates, pain at placement, adverse events and complications, acceptability, and subsequent pregnancies and abortions. Differences in nonnormal continuous variables were analyzed with the Mann–Whitney U test, and differences in dichotomous variables with the chi-square or Fisher exact tests. A P value <.05 was considered statistically significant. Group differences are presented by modified intention-to-treat and per-protocol analyses. Results: Between January 2019 and June 2022, we enrolled 179 participants, of whom 90 were assigned to the intervention and 89 to the control arm. Enrollment was prematurely stopped after an interim analysis exceeded a predefined intrauterine device expulsion rate of 20%. According to modified intention-to-treat analysis, use of intrauterine device after 6 months was 50.7% (34/67) in the intervention group vs 71.6% (48/67) in the control group (proportion difference, 20.9%; 95% confidence interval, 4.4%–35.9%; P=.02). The intrauterine device expulsion rate was 30.1% (22/73) in the intervention group vs 2.9% (2/70; P<.001) in the control group. Other adverse events were rare and patient acceptability was high in both groups. Conclusion: Intrauterine device placement within 48 hours after second-trimester medical abortion was nonsuperior in terms of the proportion of intrauterine device use after 6 months when compared with placement after 2 to 4 weeks. Placement within 48 hours after second-trimester abortion can be used in selected individuals after counseling on expulsion risk.
Keywords: contraception; copper intrauterine devices; family planning services; health services accessibility; induced abortion; intrauterine device expulsion; long-acting reversible contraception; medicated intrauterine devices; postabortion contraception; repeated abortion seekers